The annual of psychoanalysis. - Winer, Jerome A. (Taylor and Francis, 2014)
A highlight of Volume 18 is two developmental studies that attempt to situation psychoanalysis within the landscape of contemporary science: R. Galatzer-Levy and B. Cohler's examination of the developmental psychology of the self and F. Levin's consideration of psychological development and the changing organization of the Brain. Clinical studies focus on analytic stalemate (J.G. Maguire); the dream screen transference (D. Edelstein); and varieties of therapeutic alliance (B. Brandchaft and R. Stolorow).